2003
DOI: 10.17660/actahortic.2003.598.41
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Retardants for Introduction of Native Reichardia Tingitana

Abstract: The adaptation of native plants to increase the diversity of marketable ornamental species and to preserve nature has been mainly focused on trees, shrubs and perennial plants, and less so on annual plants. Reichardia tingitana is a native plant of the southeast of the Iberian Peninsula, which produces attractive flowers from March to June. This plant produces stems, which are very tall and sinuous, with one terminal inflorescence. These two last features detract from the plant's use as a bedding plant. The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…Bosch et al 2016 [46] demonstrated that a high concentration of PBZ application can reduce the plant height to a desired level. Similar results were obtained in two different studies: containerized A. graminifolia [47] and R. tingitana [48]. Our results are in agreement with the published research.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bosch et al 2016 [46] demonstrated that a high concentration of PBZ application can reduce the plant height to a desired level. Similar results were obtained in two different studies: containerized A. graminifolia [47] and R. tingitana [48]. Our results are in agreement with the published research.…”
Section: Discussionsupporting
confidence: 93%
“…In the case of PBZ treatment, we measured the lowest values. Another research study conducted with Reichardia tingitana showed that none of the PBZ doses altered the inflorescence diameter [48]. In contrast, we measured the lowest inflorescence diameter in control and PBZ-treated cyclamens.…”
Section: Discussioncontrasting
confidence: 60%
“…No PBZ dosages applied to D. barbatus × chinensis altered the corymb diameter with respect to control. In other species, both cases of no PBZ effect on flower/inflorescence size (Yewale et al, 1998;Bañón et al, 2003;Mansuroglu et al, 2009) or, on the contrary, a reducing effect (Ranney et al, 1994;Al-Khassawneh et al, 2006) have been reported. Time to flower in D. barbatus × chinensis was markedly longer in autumn-to-spring cycle than in summer-to-autumn cycle probably for climatic reasons, and some differences in flowering time were observed among the cultivars, but PBZ treatment did not affect this parameter in any season and any cultivar.…”
Section: Parametermentioning
confidence: 99%
“…There is much evidence that PBZ has an enhancing effect on leaf colour. Darker foliage was observed in PBZ-treated plants of different ornamental plants, like Cymbidium (Pan and Luo, 1994), Dicentra spectabilis (Kim et al, 1999), oleander (Bañón et al, 2001), Dianthus caryophyllus (Bañón et al, 2002), Reichardia tingitana (Bañón et al, 2003), Consolida orientalis (Mansuroglu et al, 2009), andazalea (Meijon et al, 2009). The darkening of the leaves due to PBZ has been related to their increased chlorophyll level (Pan and Luo, 1994;Nasr, 1995).…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation